The Comparison of Monocyte Human Leukocyte Antigen-D-Related (mHLA-DR) Expression Levels Between Corona Virus Disease 2019 (COVID-19) Patients and Healthy Subjects - Nabilah, Musholli Himmatun; Wardhani, Puspa; Aryati, Aryati; Hernaningsih, Yetti; Semedi, Bambang Pujo (Acta medica Indonesiana, 2023)
SARS-CoV-2 can trigger a dysfunctional immune response in COVID-19 patients and lead to immunosuppression. HLA-DR molecule expressed on the surface of monocytes, known as mHLA-DR, has been widely used as a reliable marker of immunosuppression. Downregulation of mHLA-DR reflects an immunosuppressed state. This study aimed to compare the expression level of mHLA-DR between COVID-19 patients and healthy subjects concerning immune system dysregulation that can be triggered by SARS-CoV-2 and lead to immunosuppression. This was an analytic observational study with a cross-sectional design that measured the mHLA-DR expression in EDTA blood samples from 34 COVID-19 patients and 15 healthy subjects using the BD FACSLyricTM Flow Cytometry System. The mHLA-DR examination results were expressed in AB/C (antibodies bound per cell) that were quantified using a standard curve constructed with Quantibrite phycoerythrin beads (BD Biosciences). Expression of mHLA-DR in COVID-19 patients (n = 34) were 21,201 [2,646-92,384] AB/C, with 40,543.5 [9,797-92,384] AB/C mild cases (n = 22), 21,201 [9,831-31,930] AB/C moderate cases (n = 6), and 7,496 [2,646-13,674] AB/C severe to critical cases (n= 6). Expression of mHLA-DR in healthy subjects (n = 15) was 43,161 [25,147-89,846] AB/C. Based on the Mann-Whitney U test, the mHLA-DR expression in COVID-19 patients significantly differed from the mHLA-DR expression in healthy subjects (p = 0.010). The level of mHLA-DR expression in COVID-19 patients was lower and significantly different from healthy subjects. Moreover, immunosuppression could be indicated by the decrease of mHLA-DR expression, which was below the reference range found in severe to critically ill COVID-19 patients.